Efektivitas Terhadap Pembinaan Narapidana Di Lembaga Pemasyarakatan Klas IA Makassar - Mita, Jum Juliasti; Thalib, Hambali; Salle, Salle (Universitas Pahlawan Tuanku Tambusai, 2025)
Abstract The main objective of this study is to analyze the effectiveness of prisoner development at the Class IA Correctional Institution in Makassar and to identify the factors that influence the success of the rehabilitation process. This research also aims to illustrate the extent to which the correctional institution fulfills its rehabilitative role in transforming prisoner behavior so they can be accepted back into society. The research method used is a qualitative approach with descriptive techniques. Data was collected through in-depth interviews with correctional officers and inmates, direct observation of rehabilitation activities, and documentation of relevant secondary data. This approach was chosen to gain a comprehensive and contextual understanding of the development process as it occurs in practice. The results show that prisoner development at the Class IA Correctional Institution Makassar includes personality and self-reliance development. The main supporting factors include the inmates' motivation to change, collaboration with external institutions, and the availability of competent correctional officers. However, this study also found several obstacles, such as limited budget, human resources, and facilities and infrastructure. This research recommends that the Class IA Correctional Institution in Makassar improve the quality and diversity of its development programs, enhance supporting facilities and infrastructure, and strengthen cross-sector collaboration. A more individualized approach is also needed to tailor the development process to the needs and potential of each inmate. This is essential to ensure that the correctional goals of rehabilitation can be achieved optimally. Keywords: Prisoner development, Class IA Correctional Institution Makassar.